Linking corporate social responsibility to sustainability performance: a multicase study approach in Qatari companies - Abdullah Kaid Al-Swidi; Bader Al-Esmael; Anas Abdel Karim Al Bakri; Mohammed A. Al-Hakimi; Olfa Benarfa (Discover Sustainability, 2024)
Abstract The study investigates the link between corporate social responsibility (CSR) and sustainability performance (SP) using a multi-case study approach in six Qatari firms from different industries. Specifically, it identifies how CSR practices—across philanthropy, business operations, and product responsibility—enhance environmental, social, and economic sustainability. The findings suggest that companies that adopt CSR practices achieve greater economic, environmental, and social benefits, regardless of factors like product type, business nature, and industry sector. Overall, this study provides a detailed examination of diverse sectors (construction, telecom, banking, etc.), assessing how CSR adoption varies across industries and impacts sustainability, irrespective of operational differences. Furthermore, it contributes to the literature by focusing on Qatar, a rapidly developing economy with a growing emphasis on sustainability and CSR, influenced by Qatar National Vision 2030. Therefore, the findings highlight how CSR can serve as a pathway for companies in developing economies like Qatar to achieve sustainability goals, providing actionable insights for managers to integrate CSR into their business strategies for improved economic, social, and environmental outcomes.